Identification and detection of a void under highway cement concrete pavement slabs based on finite element analysis (Rudarsko-geološko-naftni zbornik, 2019)
For a city, the construction of a road is related to the development of economy, and the construction of a road includes maintenance of the road. Cement roads have been popularized in road construction due to their low construction cost and high strength, but at the same time, road problems have arisen. In order to solve and prevent the problem of voids under highway cement concrete pavement slabs, the acoustic vibration method was used for the detection of voids under highway cement concrete pavement slabs. This method was briefly introduced and analysed with finite element analysis. Then, excitation equipment and ABAQUS software were used to perform instance analysis on the section from K08-000 to K09-000 of G325 National Road. The results showed that there were three situations, including a mild void, normal void and serious void. The degree of abrupt change of the peak amplitude of the acoustic vibration characteristic curve increased with an increase in the severity of the void under the highway cement concrete pavement slabs. The void area was obtained through calculation of the sound pressure characteristic curve data based on the finite element model, with an error between 17.0 and 21.9%. However, in road maintenance projects, this error is acceptable. In summary, the acoustic vibration method based on finite element analysis can effectively detect the position of a void under highway cement concrete pavement slabs and estimate the area.